Liquid Crystals Based on the N-Phenylpyridinium Cation—Mesomorphism and the Effect of the Anion - Jordan D. Herod; Duncan W. Bruce (Molecules, 2021)
Families of symmetric, ionic, tetracatenar mesogens are described based on a rigid, N-phenylpyridinium core, prepared as their triflimide, octyl sulfate and dodecyl sulfate salts for a range of terminal chain lengths. The mesomorphism of the individual series is described before a comparison is drawn between the different families and then more broadly with (i) neutral tetracatenar materials and (ii) related bis(3,4-dialkoxystilbazole)silver(I) salts. For the octyl and dodecyl sulfates and the related triflates reported earlier, a SmA phase is seen at shorter chain lengths, giving way to a Colh phase as the terminal chain lengthens. For the alkyl sulfate salts, an intermediate cubic phase is also seen and the terminal chain length required to cause the change from lamellar to columnar mesophase depends on the anion. Furthermore, there is an unexpected and sometime very large mesophase stabilisation seen on entering the columnar phase. All of the triflimide salts show a rectangular columnar (ribbon) phase.